Perception of chemical recycling and its role in the transition towards a circular carbon economy: A case study in Germany. (15th April 2021) - Lee, Roh Pin; Tschoepe, Manja; Voss, Raoul
Highlights: Chemical recycling (CR) as emerging theme in waste management. Qualitative insights into CR perception as a multifaceted construct in Germany. Understanding of CR in terms of inputs, process and outputs with applicability beyond Plastics-to-Plastics. Identified perceived advantages, obstacles and recommendations for implementation. Outcomes revealed policy needs and priorities to regulate CR implementation. Abstract: Chemical recycling (CR) is an emerging theme in waste management which has the potential to contribute to a low carbon, resource efficient and sustainable economy. In enabling the use of carbonaceous waste as secondary carbon feedstock to replace fossil resources for the production of organic chemicals, it could support efforts to transit carbon intensive industries from the linear to a circular carbon economy. This study investigated stakeholders' perception of CR as a multifaceted construct. Objective is to complement technological-economical-ecological evaluations of CR innovations, and inform socio-political discussions about its role in the transformation of carbon intensive and dependent industries. An exploratory case study approach consisting of a qualitative survey and a semi-structured workshop discussion is utilized to assess the perception of CR and its perceived role in the transformation of Germany's chemical and waste management industries. Findings enabled insights into how CR is understood, what are seen as desirable inputs and outputs, perceived advantages compared to conventional recycling and thermal treatment as well as obstacles to its implementation. Additionally, the outcomes revealed policy and regulatory needs which will have to be addressed in order to successfully implement CR as a complementary building block of sustainable waste management. Study findings thus provide valuable information and insights to support managerial decision-making as well as the development and prioritization of measures by policymakers to regulate the implementation of CR technologies.